2019
DOI: 10.1590/0037-8682-0292-2018
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, open-label clinical trial comparing the long-term effects of miltefosine and meglumine antimoniate for mucosal leishmaniasis

Abstract: Introduction: The treatment of mucosal leishmaniasis (ML) is difficult due to the toxicity and route of administration of standard drugs. Miltefosine is an oral agent used for leishmaniasis treatment; however, no data exist regarding its use for ML in Brazil. In this study, we aimed to evaluate the efficacy of miltefosine for ML treatment compared to that of pentavalent antimonial in a pilot study. Methods: We performed a randomized clinical trial with two parallel groups. The tested intervention consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…The most common side effects are related to gastrointestinal disorders, such as nausea and diarrhoea, which do not interrupt treatment. Moreover, nephrotoxicity is rare (Sundar et al, 2002;Chrusciak-Talhari et al, 2011;Dorlo et al, 2012b;Sampaio et al, 2019;Wall et al, 2019). In addition, preliminary studies and case reports presenting promising results have also used miltefosine to treat patients with bone and joint infections caused by L. prolificans, which demonstrate that it could be applied in the clinic with no significant side effects (Kesson et al, 2009;Quaesaet et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The most common side effects are related to gastrointestinal disorders, such as nausea and diarrhoea, which do not interrupt treatment. Moreover, nephrotoxicity is rare (Sundar et al, 2002;Chrusciak-Talhari et al, 2011;Dorlo et al, 2012b;Sampaio et al, 2019;Wall et al, 2019). In addition, preliminary studies and case reports presenting promising results have also used miltefosine to treat patients with bone and joint infections caused by L. prolificans, which demonstrate that it could be applied in the clinic with no significant side effects (Kesson et al, 2009;Quaesaet et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…ML is more severe and difficult to treat than CL ( Burza et al., 2018 ; Chakravarty and Sundar, 2019 ; Sampaio et al., 2019 ); therefore, it is expected that patients with CL would have a higher cure rate, even after a shorter duration of treatment ( Figure 2 ). Indeed, the multivariate analysis showed that patients with cutaneous lesions had a higher cure rate in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Miltefosine is the first oral drug with efficacy against leishmaniasis, and it has been used since 2002 for the treatment of both visceral ( Sundar et al., 2002 ) and mucocutaneous leishmaniasis. It affects the phospholipid membrane integrity and mitochondrial function of microorganisms ( Sundar et al., 2002 ; Soto et al., 2004 ; Chrusciak-Talhari et al., 2011 ; Sampaio et al., 2019 ). It also has an indirect effect by acting as an immunomodulator against Leishmania, promoting the production of IFN-γ, TNF-α and IL-12 and stimulating phagocytosis and the Th1 pathway ( Santarem et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…15 In Brazil, using oral miltefosine at 1.3-2 mg/kg/day for 28 days, 11/12 patients with ML were cured at 90 days after treatment, and on examination after 4 years, 16/18 patients were considered cured. 16 In a pilot study in Argentina, seven of eight patients with ML were cured using a dose of 2.5-3.3 mg/kg/daily. 17 Not all Leishmania species are equally susceptible to miltefosine.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] In the four prior clinical studies that were carried out, L. braziliensis was the predominant infecting species. [14][15][16][17] In a systematic review published in 2013, at 6 months, a significant difference was noted in the rate of complete cure favoring miltefosine when compared with meglumine antimoniate for L. panamensis and L. guyanensis. 13 In Ecuador, miltefosine has never been used to treat ML, and this is the first time to show here the efficacy of miltefosine in an infection due to L. guyanensis; in a case report of diffuse CL leishmaniasis caused by Leishmania mexicana, miltefosine failed to cure both clinically and parasitologically.…”
Section: Discussionmentioning
confidence: 99%